Oxford handbook of orthopaedics and trauma - Bowden, Gavin (Oxford : Oxford University Press, 2010)
This handbook provides easily accessible information on orthopaedics and trauma, clearly presenting the salient features of a range of conditions and their treatment, and enabling junior doctors and students to confidently apply the knowledge to clinical activities.
1. Orthopedic history and examination -- 2. Orthopedic investigations -- 3. Orthopedic management -- 4. Preoperative care -- 5. Biomaterials and implants -- 6. Anatomy -- 7. Surgical approaches -- 8. Adult orthopedics -- 9. Adult trauma -- 10. Pediatric orthopedics -- 11. Pediatric trauma -- 12. Rehabilitation
Includes bibliographical references and index
Keywords: Musculoskeletal system -- Wounds and injuries; Orthopedic surgery; Musculoskeletal System -- injuries; Handbooks; Musculoskeletal Diseases; Orthopedic Procedures